(untitled) (Economics and region, 2025)
The article analyzes the integration of ESG strategy into global ratings, in particular, which characterize the level of uncertainty of sustainable development, the level of uncertainty of world trade policy. The presented graphical analytical studies reflect the ratings and the status of ESG strategy implementation and assess the impact on the components of environmental, social, and management aspects on the development of both European and South and North American countries. In addition, the value of the sustainable development uncertainty index assessment indicator is generalized, which allows us to assess the level of risks and the associated uncertainty, to assess how much instability in the external or internal environment can affect the achievement of ESG goals. The dynamics of the profitability level of agricultural enterprises over the past ten years was analyzed, which made it possible to assess the impact on the level of achievement of individual strategic goals of sustainable development. Based on the conducted studies, the content of the structural elements of ESG strategy and the motives and prospects for their implementation into the management system of agribusiness enterprises are summarized. In particular, it was determined that the integration of ESG criteria will allow agribusiness enterprises not only to minimize environmental and social risks, but also to create added value through the implementation of innovative technologies, attracting investments and increasing reputational capital. For Ukrainian agricultural enterprises, a promising direction is the implementation of structural elements of the ESG strategy to enhance investment attractiveness in the post-war period to restore the potential of business structures in the agricultural sector. In particular, through the environmental component, it is possible to implement practices for the rational use of natural resources, reduce greenhouse gas emissions, optimize the waste management system and switch to renewable energy sources; the social aspect will focus on ensuring safe working conditions, developing human resources, supporting local communities and adhering to the principles of fair labor policies; the managerial (corporate) component includes increasing the transparency of business processes, forming ethical standards of corporate behavior and implementing effective risk management mechanisms.